Reproductive Output and Seasonality of Limnoperna fortunei - Boltovskoy, Demetrio (2015)
Fil: Boltovskoy, Demetrio. Instituto de Ecología. Genética y Evolución de Buenos Aires (IEGEBA). Universidad de Buenos Aires; Argentina